Mathematical image processing University of Orlâeans, France, March 29th - April 1st, 2010 - Bergounioux, Maèitine (Springer proceedings in mathematics, 2011)
The contributions appearing in this volume are a snapshot of the different topics that were discussed during the conference. They mainly concern, image reconstruction, texture extraction and image classification and involve a variety of different methods and applications. Therefore it was impossible to split the papers into generic groups which is why they are presented in alphabetic order. However they mainly concern : texture analysis (5 papers) with different techniques (variational analysis, wavelet and morphological component analysis, fractional Brownian fields), geometrical methods (2 papers ) for restoration and invariant feature detection, classification (with multifractal analysis), neurosciences imaging and analysis of Multi-Valued Images.